Acupressure on the xuehai point (SP10) reduces menstrual pain in students - Khayati, Nikmatul; Febrianti, Rizka; Machmudah, Machmudah; Rejeki, Sri (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Background: Dysmenorrhea is a pain in the abdomen that is felt before the onset of menstruation until the initial period of the menstrual process. Pain occurs due to uterine ischemia. Pain during menstruation (dysmenorrhea) varies in level so that different manifestations are felt. Pain may radiate from the abdomen to the waist. Dysmenorrhea can disrupt daily activities, sleep disturbances, learning and concentration disorders, and decrease appetite. Acupressure is a non-pharmacological therapy to treat dysmenorrhea. This study aims to determine the effectiveness of acupressure on the level of menstrual pain in college students. Method: The type of research is quasi-experimental with a one-group pre-post test design. The number of samples is 18 respondents. The sampling technique is non-probability sampling with a purposive sampling approach. Each respondent measured the level of pain before and after therapy to determine the effectiveness of acupressure therapy. Result: The results showed that the level of menstrual pain after acupressure decreased by 1.444 points. With a p-value (0.000) with a significance p-value of less than 0.05, it can be concluded that the acupressure action is effective. Acupressure on the Xuehai point (SP10) is effective against the level of menstrual pain (dysmenorrhea) significantly. Analysis: The acupressure mechanism at the Xuehai (sp10) point causes a deqi reaction (numbness, heaviness, tension) so that it stimulates the release of neurotransmitters that will enter the blood circulation which circulates throughout the body towards sensory nerves and stalked cells which can inhibit nerve impulses to the hypothalamus-pituitary. Discussion: Researchers suggest that students can apply acupressure therapy when experiencing dysmenorrhea as an alternative option to overcome the pain they feel. Abstrak: Latar belakang:Dismenore adalah nyeri pada perut yang dirasakan sebelum dimulainya menstruasi sampai dengan awal periode proses menstruasi. Nyeri terjadi karena iskemia uterus. Nyeri saat menstruasi (dismenore) berbeda-beda tingkatannya sehingga dirasakan manifestasi yang berbeda. Nyeri dapat menyebar dari perut ke pinggang. Dismenore dapat mengganggu aktivitas sehari-hari, gangguan tidur, gangguan belajar dan konsentrasi, serta penurunan nafsu makan. Akupresur merupakan terapi nonfarmakologis untuk mengatasi dismenore. Penelitian ini bertujuan untuk mengetahui efektivitas akupresur terhadap tingkat nyeri haid pada mahasiswa. Metode:Jenis penelitian ini adalah eksperimen semu dengan desain one group pre-post test design. Jumlah sampel adalah 18 responden. Teknik pengambilan sampel adalah non-probability sampling dengan pendekatan purposive sampling. Setiap responden mengukur tingkat nyeri sebelum dan sesudah terapi untuk mengetahui efektivitas terapi akupresur. Hasil:Hasil penelitian menunjukkan bahwa tingkat nyeri haid setelah akupresur mengalami penurunan sebesar 1,444 poin. Dengan p-value (0,000) dengan signifikansi p-value kurang dari 0,05 maka dapat disimpulkan bahwa tindakan akupresur efektif. Akupresur pada titik Xuehai (SP10) efektif terhadap tingkat nyeri haid (dismenore) secara signifikan. Analisis:Mekanisme akupresur pada titik Xuehai (sp10) menyebabkan reaksi deqi (mati rasa, berat, tegang) sehingga merangsang pelepasan neurotransmiter yang akan masuk ke peredaran darah yang beredar ke seluruh tubuh menuju saraf sensorik dan sel-sel penguntit yang dapat menghambat saraf impuls ke hipotalamus-hipofisis. Diskusi:Peneliti menyarankan agar mahasiswa dapat menerapkan terapi akupresur saat mengalami dismenore sebagai alternatif pilihan untuk mengatasi nyeri yang dirasakan.